Evolution of Pediatric Urology at Sindh Institute of Urology and Transplantation - Sultan, Sajid (Frontiers in Pediatrics, 2014)
Sindh Institute of Urology and Transplantation (SIUT) was started in 1972 as an eight bedded department of genitourinary surgery in a government hospital by it’s pioneer and present director Syed adeeb ul Hassan Rizvi. Responding to the socioeconomic dynamics and the needs of the patient population the facility grew into the largest tertiary care Urology, Nephrology and Transplant centre of South East Asia. One of the salient component has been the evolution of the Department of Paediatric Urology which in itself has shown a tremendous growth into an internationaly recognized centre for Paediatric Urology services taking care of all aspects including centre of excellence for paediatric stone disease. The guiding mission of this institute remains to provide free medical services at zero cost without any discrimination to all who come to its doorstep and matching with high standard of care without compromising the dignity and self respect. This institute highlights the fact that lack of resources is no excuse and is a role model for developing countries, where national and international support, motivation and cooperation can offer more advanced and better quality medical services to our children.